The 26S Proteasome Is Required for the Maintenance of Root Apical Meristem by Modulating Auxin and Cytokinin Responses Under High-Boron Stress - Sakamoto, Takuya; Sotta, Naoyuki; Suzuki, Takamasa; Fujiwara, Toru; Matsunaga, Sachihiro (Frontiers in Plant Science, 2019)
Boron (B), an essential micronutrient, causes adverse effects on the growth and development of plants when highly accumulated. By the analysis of Arabidopsis mutants hypersensitive to high-boron (high-B) stress, we have shown that 26S proteasome (26SP) is required to maintain the morphology of the root apical meristem (RAM) under high-B stress. To further understand the molecular function of 26SP in tolerance to high-B stress in the RAM, in this study we investigated the pathways regulated by 26SP using a 26SP subunit mutant, rpt5a, which is hypersensitive to high-B stress. Expression of RPT5a was induced by high-B stress in the entire RAM accompanied by its strong expression in the stele, including the stem cells. Analysis of stele organization in the rpt5a mutant revealed that 26SP is especially important for maintenance of the stele under high-B stress condition (3 mM B treatment). Expression analyses of an auxin-response reporter revealed that auxin responses were enhanced in the stele and the stem cell niche by high-B stress, especially in the rpt5a mutant. In contrast, the expression of TCS::GFP representing cytokinin signaling in the stem cell niche was unchanged in the wild type and extremely weak in the rpt5a mutant, irrespective of B condition. The drastically aberrant auxin and cytokinin responses in the rpt5a mutant under high-B stress were supported by transcriptome analysis using root tips. These results suggest that the collapse of hormonal crosstalk in the stele including the stem cells occurred in the rpt5a mutant, especially under high-B stress. Treatment with the auxin signaling inhibitor α-(phenyl ethyl-2-one)-indole-3-acetic acid (PEO-IAA) reduced sensitivity to high-B stress in the wild type and restored the RAM morphology in the rpt5a mutant under the high-B stress condition. In addition, cytokinin treatment conferred the rpt5a mutant with tolerance to high-B stress in RAM morphology. It is concluded that 26SP containing RPT5a is required for maintenance of auxin/cytokinin balance in the stele, which is crucial for preventing defects in RAM morphology under high-B stress.